The genome-wide identification of mitogen-activated protein kinase kinase (MKK) genes in Yesso scallop Patinopecten yessoensis and their expression responses to bacteria challenges. Issue 2 (August 2015) - Zou, Jiajun; Wang, Ruijia; Li, Ruojiao; Kong, Yifan; Wang, Jing; Ning, Xianhui; Zhang, Lingling; Wang, Shi; Hu, Xiaoli; Bao, Zhenmin
Abstract: Mitogen-activated protein kinase kinases (MKK) are the essential components of the evolutionarily conserved MAPK signaling cascade, which regulates a variety of cellular activities and innate immune responses. Although MKK genes have been extensively studied in various vertebrate and invertebrate species, they have not been systematically characterized in bivalves. In this study, we identified and characterized five MKK genes ( PyMKK1/2, PyMKK4, PyMKK5, PyMKK3/6 and PyMKK7 ) in the Yesso scallop ( Patinopecten yessoensis ). Phylogenetic and protein structural analyses were conducted to determine their identities and evolutionary relationships. To gain insights into the possible roles of MKK genes during scallop innate immune responses, quantitative real-time PCR (qRT-PCR) was used to investigate their expression profiles during different developmental stages in samples taken from healthy adult tissues and hemocytes after Micrococcus luteus and Vibrio anguillarum bacterial infections. The Yesso scallop MKK s ( PyMKK s) were found to have highly conserved structural features compared to the MKK genes from other invertebrate species. Using qRT-PCR analysis, three distinct expression patterns were detected among the PyMKK s over the course of ten different developmental stages. In adult scallops, the majority of the PyMKK s were highly expressed in mantle, gill, muscle and hemocytes. The differential expression patterns of the five PyMKK s after M. luteus (Gram-positive) and V. anguillarum (Gram-negative) bacterial infections suggested their possible involvement in the innate immune response and provide the foundation and resource for the further study on innate immune response of MAPK signal pathway in mollusk. Highlights: We identified and characterized five PyMKK genes in Yesso scallop. Phylogenetic analysis confirmed their identities and nomenclature. Differential expression of PyMKKs was observed after the bacterial infection. Expression correlation results implied the potential interaction between PyMKKs.